SAFEGUARDING MOTORIZED VEHICLES WITH ARM VIBRATORS USING ULTRASONIC SENSORS AND BLUETOOTH - Ariyanto, Riski; Fora, Rony Haendra Rahwanto (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2019)
Safeguarding motorized vehicleswith arm vibrators using ultrasonic sensorsand Bluetooth is an innovation in safetysystems on motorized vehicles (Motorbikes).This tool uses a proximity sensor and armvibrator, which this tool will work if themotor vehicle (motorcycle) is too close to theobject in front of it. When the sensor hasdetected an object, the vibrator willautomatically vibrate the arm. When thevibrator vibrates, that will be a sign that thedriver is too close to the vehicle in front ofhim, so the driver will maintain a safedistance from other vehicles in front. Theobjectives of this research activity includeknowing the concept of developing a safetysystem on motorized vehicles that can preventaccidents, when motorists are negligent incontrolling the speed of their vehicles on thehighway.